2005
DOI: 10.1002/dvdy.20289
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of cDNAs and the differential expression of A‐type cyclins and Dmc1 during spermatogenesis in the Japanese eel, a teleost fish

Abstract: We cloned A-type cyclins (cyclins A1 and A2) and Dmc1 cDNAs from the eel testis. Cyclin A1 mRNA was predominantly expressed in the livers, ovaries, and testes of the eels. In contrast to cyclin A1 mRNA, a very high expression of cyclin A2 mRNA was observed in the brains, livers, kidneys, spleens, ovaries, and testes of the eels. Dmc1 mRNA was predominantly expressed in the testes and ovaries; expression in the brain was also detected. In the eel testis, a few type-A spermatogonia incorporating 5-bromo-2 -deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
2
18
1
2
Order By: Relevance
“…The genes vasa and sox2 are expressed in spermatogonia and spermatocytes of Nile tilapia (Kobayashi et al 2002, Supplementary Figure 4, see section on supplementary data given at the end of this article) while dmc1 is expressed only in meiotic cells (Kajiura- Kobayashi et al 2005). In s-males the relative abundance of the analysed germ line-specific genes was higher than in d-males (Fig.…”
Section: Gene Expression Analysis Of Testes From Dominant and Subordimentioning
confidence: 90%
“…The genes vasa and sox2 are expressed in spermatogonia and spermatocytes of Nile tilapia (Kobayashi et al 2002, Supplementary Figure 4, see section on supplementary data given at the end of this article) while dmc1 is expressed only in meiotic cells (Kajiura- Kobayashi et al 2005). In s-males the relative abundance of the analysed germ line-specific genes was higher than in d-males (Fig.…”
Section: Gene Expression Analysis Of Testes From Dominant and Subordimentioning
confidence: 90%
“…In that study, Dmc1 mRNA was abundantly expressed in the testes and ovaries, and lower expressed in the brain. In situ hybridization revealed that Dmc1 of A. japonica was localized only in primary spermatocytes, implying its important role during the initial stages of spermatogenesis (19).…”
Section: Rt-pcr and Tissue Distribution Analysismentioning
confidence: 99%
“…Recently, the full length Dmc1 cDNA was cloned from the testis of the Japanese eel (Anguilla japonica) (19). In that study, Dmc1 mRNA was abundantly expressed in the testes and ovaries, and lower expressed in the brain.…”
Section: Rt-pcr and Tissue Distribution Analysismentioning
confidence: 99%
“…The role of Dmc1 in promoting interactions between homologous chromosomes appears to be conserved from yeast to mammals (Tarsounas et al, 1999). On the other hand, our recent study indicates that the Dmc1 protein is expressed in meiotic prophase specifically during spermatogenesis in the teleost fish Anguilla japonica (Kajiura-Kobayashi et al, 2005).…”
Section: Introductionmentioning
confidence: 91%
“…To generate antibodies against Dmc1, we used as the immunizing antigen an oligopeptide that corresponds to the C-terminal amino acid sequence (tilapia Dmc1: AB18246, Kajiura-Kobayashi et al, 2005) predicted from tilapia Dmc1 cDNA, with the addition of a cysteine at the Nterminus to facilitate linkage to the carrier protein, as described previously (Kobayashi et al, 1996). Conjugation of the antigen to bovine serum albumin (BSA, fraction V; Sigma Chemical Co., St. Louis, MO) as the carrier protein was performed as described previously .…”
Section: Production Of the Anti-dmc1 Antibodymentioning
confidence: 99%